Numerical analysis of sound radiation from rotating discs. (3rd March 2020) - Maeder, M.; D'Auria, R.; Grasso, E.; Petrone, G.; De Rosa, S.; Klaerner, M.; Kroll, L.; Marburg, S.
Abstract: The analysis of sound radiation from rotating elastic discs, e.g. saw blades, is an interesting research topic. Especially for people who work in the vicinity of such machines, health related issues with respect to noise exposure levels gain more and more awareness. Therefore, the industry is faced with the challenge of developing quieter products in order to improve the working environment and to extend the time a worker can use these tools before a harmful situation arises. Moreover, less noise emission means less energy consumption and therefore a higher productivity. In this paper, the authors investigate the sound radiation from a rotating disc where the sound power is used as a global measure for the acoustic performance. Different methods for calculating the sound power of a spinning saw blade are compared. These are a fully coupled finite element approach, a hybrid finite element/boundary element approach, a simplified form of the Rayleigh integral known as the lumped parameter model, and the equivalent radiated sound power. The results show good agreement between the costly full models and those utilizing approximation methods which can save remarkable computational costs. The proposed frame can be used in optimization procedures for developing quieter saw blades and other rotating discs. Furthermore, the paper discusses mode splitting which is a well-known phenomenon for rotating machinery. For this, the results of sound radiation are investigated with respect to the question whether mode splitting is actually audible.